High day-to-day and diurnal variability of oxidative stress and inflammation biomarkers in people with type 2 diabetes mellitus and healthy individuals - Alistair R. Mallard; Siri Marte Hollekim-Strand; Charlotte Björk Ingul; Jeff S. Coombes (Taylor & Francis Group, 2020)
Objective: Assess the variability and differences in oxidative stress, antioxidant, and inflammatory biomarkers in people with type 2 diabetes mellitus (T2D) and healthy controls. Methods: Ten men and women diagnosed with T2D and ten healthy matched controls (CON) were recruited. Participants had venous blood taken at six different time points on different days, three in the morning (after overnight fast) and three in the afternoon. Inflammation (IL-6, 8, 10 and TNF-α), oxidative stress/antioxidant biomarkers (F2-isoprostanes, protein carbonyls, total antioxidant capacity (TAC), glutathione peroxidase activity, IL-6, 8 & 10 and TNF-α) were assessed. Results: Biomarker concentrations were similar between groups. There was large variability in nearly all biomarkers for both groups. For inflammatory measures, intra-individual coefficients of variation (CV) ranged from 64.0-92.1% and 100.9-259.0% for inter-individual differences. CVs for oxidative stress markers were lower (7.4-31.2% for intra-individual and 8.6-43.0% for inter-individual). TAC had the lowest intra-individual CV - 7% for T2D and 8% for CON. Protein carbonyls were more variable in the afternoon (34% CV) compared to morning (24% CV) in CON. IL-6 intra-individual CV was different between groups for afternoon measurements (93% T2D, 60% CON). Conclusion: Oxidative stress and inflammatory biomarkers show considerable variation in both T2D and healthy populations. Trial registration: ClinicalTrials.gov identifier: NCT01206725.